WATER ROLE ON DIELS-ALDER REACTION OFPRENYLATED FLAVONOIDFORMATIONIN Boesenbergia pandurata: MECHANISM STUDY - Rusdipoetra, Rahmanto Aryabraga; Kautsar Ul Haq (Jurnal Kimia Riset, 2023)
Panduratin A is a prenylated flavonoid derivative from Boesenbergia pandurata with many potential biological activities. The biogenesis of this compound and its derivatives is believed to involve a Diels-Alder reaction between monoterpenoid and chalcone derivatives. This study provides insight into modeling biogenesis through the Diels-Alderreaction for Panduratin A and derivatives biosynthesis. We are using M06-2X/6-31G(d)//PM6 level of theory to explore the potential energy surfaces, asynchronicity degree, and global electron density transfer. Explicit water was applied to mimic physiological conditions. Contrary to the fact that water accelerates this reaction through hydrogen bonding catalysis, we found that water could slow this reaction. These results suggest that this reaction proceeds very slowly under physiological conditions, and enzymes catalyze this reaction.